Abs. Issue 1 (November 2015) - Tashireva, L.; Denisov, E.; Savelieva, O.; Zavyalova, M.; Kaigorodova, E.; Slonimskaya, E.; Perelmuter, V.
Abstract : Background: Intratumoral heterogeneity contributes significantly to the effectiveness of cancer treatment and outcome (Ng C.K., Pemberton H.N., Reis-Filho J.S., 2012). Previously the phenomenon of intratumoral morphological heterogeneity was demonstrated in breast cancer and it was found that the presence of alveolar structures in breast tumors is associated with high frequency of lymphogenic metastasis (Zavyalova M.V. et al., 2013a; Zavyalova M.V. et al. 2013b; Denisov E.V. et al., 2014). Tumor microenvironment (ME) is a key factor in determining the properties of the invasive and metastatic potential of the tumor and seems to be also heterogeneous. Analysis of the ME in patients with different solid tumors reveals that the majority of tumors show a T cell–infiltrated phenotype. Macrophages, fibroblasts, dendric cells etc. are also located in the ME and show their effects. The aim of this work was to determine the expression of key markers of cells which are presented in the ME of the various morphological structures. Materials and methods: A 49 year-old patient (IC NST, luminal A, T1NxMx, grade 2) was enrolled in this study. The ME of tubular (hollow-like), alveolar (morula-like), trabecular, solid structures/patterns, and discrete (small) groups of tumor cells were isolated from invasive breast carcinoma NST ( n = 1) using laser microdissection (PALM, Carl Zeiss). RNA was extracted using RNeasy Plus Micro Kit (Qiagen, USA) according to the manufacturer's instructions. cDNA was synthesized, ligated, and amplified using QuantiTect Whole Transcriptome Kit (Qiagen, USA) according to the manufacturer's instructions. The gene expression of ALCAM, Bcl6, CD3E, CD4, CHI3L2, CHID1, FAP, CD244, FoxP3, RORc, CD8, GATA-3, TBX21, EPCAM, CD79, CD206, CD209, IL12, CXCL11, TGFb, IL10 was analyzed using qRT-PCR and normalized to ACTB1 gene and normal tissue. Results: We showed the prevalence of gene expression in the ME of alveolar and solid structures. At the same time only one gene (GATA-3) was found to be expressed in the ME of trabecular structures and discrete groups of tumor cells. In the ME of alveolar structures we found transcripts involved in Th1-response (CD3E, CD4 and CD8). In addition, expression of GATA-3, TGFb, FAP (fibroblast marker) and CD79 (B-lymphocyte marker) genes linked with the Th2-response was also shown in the ME of alveolar structures. In the ME of solid structures we detected expression of CD3E gene (lymphocyte marker), transcription factors of Th1, Th2 and Th17 cells (TBX21, GATA-3 and RORc genes, respectively), NK cell marker (CD244), fibroblast marker (ALCAM), and IL12 gene. Conclusion: The obtained data demonstrate heterogeneity of the tumor microenvironment in invasive breast carcinoma NST. Inflammatory (Th1-response) and anti-inflammatory (Th2) reactions were observed both in the ME of alveolar and solid structures. The ME of trabecular structures and discrete groups of cancer cells showed only inflammatory marker. Functional activity of the ME of alveolar structures is determined by expression of TGFb gene, which is involved in anti-inflammatory response, invasion and progression, while in the microenvironment of solid structures IL-12 gene, a key cytokine of Th1 response is expressed.